Two novel species of Lecanora genus (Ascomycota, Lecanoraceae) from Western Himalaya, Pakistan - Noor, Atika; Saba, Malka; Akram, Wajahat; Ullah, Mohsin; Asif, Muhammad (Phytotaxa, 2025)
During this study we investigate two new species of crustose lichen Lecanora ahmadii sp. nov. and Lecanora haripurensis sp. nov. from district Haripur and Murree, Pakistan. Based on morphological and molecular phylogenetic analysis. Lecanora haripurensis sp. nov. is characterized by light greyish white to rough white thallus, lecanorine, black sessile, irregular apothecia, falls in sister clade to species Lecanora epibryon. The other specimen Lecanora ahmadii sp. nov. is characterized by verruculose dark greyish green thallus with light brown apothecia and phylogenetic resemblance to Lecanora pseudargentata. Thus, two new species have been added to lichen flora of Pakistan. They are new additions to science as well.